Perancangan Aplikasi Sistem Absensi Guru Dan Karyawan Berbasis Web Sekolah Menengah Kejuruan - Putra, Fraska Drahma; Anwar, Nizirwan (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
The development of information technology is quite extensive and global and has had a changing impact on all aspects ofhuman life. In the field of education, information technology is very necessary in order to support the performance ofeducation so that it can be useful in building an intelligent and competitive generation, one of which is at Global PersadaVocational School. Based on observations, Global Persada Vocational School does not yet have a teacher and employeeattendance system for processing teacher absence data. The obstacles that are often encountered in manual processing ofabsentee data are that it is very slow, ineffective, and makes it difficult for school principals to manage and check data onteachers who are present, and is even prone to losing absenteeism recap data. The aim of this research is to design andbuild a Web-based attendance system for processing teacher and employee attendance data for Global PersadaVocational School to make it easier to process teacher and employee attendance data. In building the teacher andemployee attendance system, the author used the SDLC method with the Waterfall model in designing the system andproduced a system with a simple interface that can help present accurate and relevant value data processing information.